Analysis and Modelling on Radiated Noise of a Typical Fishing Boat Measured in Shallow Water Inspired by AQUO Project’s Model - PENG, Zilong; FAN, Jun; WANG, Bin (Archives of Acoustics, 2018)
The shipping noise near channels and ports is an important contribution to the ambient noise level, and the depth of these sites is often less than 100 m. However less attention has been paid to the measurement in shallow water environments (Brooker, Humphrey, 2016). This paper presents extensive measurements made on the URN (underwater radiated noise) of a small fishing boat in the South China Sea with 87 m depth. The URN data showed that the noise below 30 Hz was dominated by the background noise. The transmission loss (TL) was modelled with FEM (finite element method) and ray tracing according to the realistic environmental parameters in situ. The discrepancy between the modelled results and the results using simple law demonstrates both sea surface and bottom have significant effect on TL for the shallow water, especially at low frequencies. Inspired by the modelling methodology in AQUO (Achieve QUieter Oceans) project (Audoly, Enrico, 2015), a predicted model applied to a typical fishing boat was built, which showed that the URN at frequencies below and above 100 Hz was dominated by non-cavitation propeller noise and mechanical noise, respectively. The agreement between predicted results and measured results also demonstrates that this modelling methodology is effective to some extent.